Characteristics of Referral Patients with Gestational Trophoblastic Neoplasia in Dr. Hasan Sadikin General Hospital Bandung - Kemala Isnainiasih Mantilidewi; Aditya Rifandi Zaenudin; Ali Budi Harsono; Anita Deborah Anwar; Jessica Kireina (Indonesian Journal of Cancer, 2023)
Background: : Gestational trophoblastic disease (GTD) is a heterogeneous group of lesions caused by abnormal trophoblast proliferation and the malignant form is called gestational trophoblastic neoplasia (GTN). Dr. Hasan Sadikin General Hospital, located in Bandung, West Java, is one of the main cancer referral hospitals in Indonesia. Consequently, the characteristics of GTN patients in this hospital can represent the general population in the province. This study aimed to elaborate on the characteristics of referral patients with GTN in Dr. Hasan Sadikin General Hospital.Methods: : Medical records of post-molar GTN patients in Dr. Hasan Sadikin General Hospital from between January 2019 to December 2020 were collected and analyzed. GTN was diagnosed according to the International Federation in Gynecology and Obstetrics (FIGO) criteria. Additionally, both the sociodemographic and clinical characteristics of patients were evaluated.Results:  The results showed that among the 160 participants in this study, the overall mean age was 33±8.7 years, with a mean βhCG level of 241,461.81±630,557.90 mIU/mL. Moreover, approximately 16.3% had gestosis and 5% were diagnosed with hyperthyroidism. The majority of post-molar observations at the hospital were not carried out according to standards, with only 8.1% of patients receiving optimal surveillance. About 56.8% visited the hospital due to vaginal bleeding, while most histopathological results showed complete hydatidiform moles (44.4%), and choriocarcinomas (16.3%). Most of the patients were diagnosed as stage I (81.9%), had lowrisk FIGO scores (80.6%), and were treated with methotrexate (80.6%).Conclusions:  GTN patients in Dr. Hasan Sadikin General Hospital showed clinical characteristics consistent with previous studies. The low percentage of patients receiving optimal post-molar surveillance could cause delayed referral. This suboptimal surveillance might be due to the high cost of βhCG testing, lack of facilities, and low patient compliance in West Java